CYBERBULLYING: INTIMIDAÇÃO SISTEMÁTICA, CONSTRANGIMENTO VIRTUAL E CONSEQUÊNCIAS JURÍDICAS (Revista Direitos Humanos e Democracia, 2020)
This article aims to understand the legal relevance of the discussion on cyberbullying. Its hypothesis is that the current forms of digital social relations lead to the possibility of abuse, similarly to what happens in person — however, in a way that is enhanced by the complexity, reach and speed that social networks offer. As a result, relationships in social networks replicate abusive practices that also occur physically, causing moral and existential damage. In view of this, it is necessary that there are careful analyzes and practices of this type of practice, in a joint effort between the State, schools, families and social media controls, so that such practices can be restrained. Methodology: hypothetical-deductive procedure method, with a qualitative and technical approach to bibliographic-documentary research.
Keywords: cyberspace; cyberbullying; embarrassment; virtual crimes